The correlation between students learning strategies and their achievement in writing skill at second semester English Department students of Unisma. - Indah Permatasari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: Writing is one of the skills in learning English. The students can express their ideas on writing. The students can share their creativity and improve their knowledge by writing. But writing is complicated for most students. The researchers identified many problems facing students in learning writing based on interview with students. The problems often faced by students are difficult to develop ideas, lack of motivation to read, lack of vocabulary, and errors in using grammar. For solving the problem, the students should have specific learning strategies in learning writing.This study uses quantitative research design. In this research, the researcher discuss of following the research problem: “Is there any correlation between students learning strategies and their achievement in writing skill at second semester English Department students of Unisma?”. The objective of this study to find out if there is correlation between students learning strategies and their achievement in writing skill.The sample of this study was the students of English Department, especially the second semester students. The participants of this study were 33 students. The data were collected using questionnaire adopted from Raoofi, Miri, Gharibi, & Malaki (2017) and writing score. The data analyzed using Stastical Package for Social Science (SPSS) 17.00 version.The result of this study show that the null hypotheses is rejected. In other words, this research showed that there is correlation between students learning strategies and their achievement in writing skill. The level sig. (2-tailed) was lower than the level of significant (0.05). It can be said that the alternative hypotheses is accepted. It means that the students who used strategy in learning writing can improve their achievement in writing skill. If students practice a lot on the strategies used, they will be more confident and successful in learning. Key Words: Learning strategies, achievement, writing